ANALISIS KEMAMPUAN LITERASI NUMERASI BERDASARKAN KECERDASAN LOGIS-MATEMATIS PADA PEMBELAJARAN MATEMATIKA - Pertiwi, Hana; Suntari, Yustia; Dallion EW, Engga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This scientific work discusses numeracy literacy abilities based on logical-mathematical intelligence in elementary school students' mathematics learning. This research was motivated by a lack of understanding of numeracy literacy in Mathematics learning and differences in levels of logical-mathematical intelligence in elementary school students. Based on international studies, namely the Program for International Student Assessment (PISA), Indonesia was ranked 68th out of 74 countries that participated in the program in 2009. Apart from that, in 2012, Indonesia was ranked 64th out of 65 countries. Then in 2015, Indonesia was ranked 63rd out of 72 countries that participated in the program. Most recently, in 2018, Indonesia's ranking was at level 68 out of 74 countries. This data shows that the literacy culture of students in Indonesia is still low. Therefore, this research aims to analyze the relationship between logical-mathematical intelligence and numeracy literacy in elementary school students' mathematics learning. The method used in this research is literature study, namely finding ideas and facts through library research or tracing sources of previous scientific writing. From the research results, it was found that the numeracy literacy abilities of students in elementary schools were still relatively low and there were differences between the numeracy literacy abilities of students with high and low logical-mathematical intelligence.